1. INNOVATION: ROBUST AIR POWER CAPABLE OF CONTINUAL MARITIME OPERATIONS AND REINFORCED NATIONAL CYBER STRATEGY TO PROTECT NATIONAL SECURITY - Budiman , Arief (Jurnal TNI Angkatan Udara, 2023)
Clausewitz‘s thought that the character of war is influenced by technology is still relevant to theStrategic Competition (Great Power Competition). The competition and the new character of war couldimpact Indonesia through the Sino-India and the Taiwan scenario both in peacetime and wartime. Anyattempt to use force against U.S. friends and allies would propel the US to use conventional militarypower and even a limited nuclear.1 Therefore it will impact the population and create two challengesfor Indonesia. The challenge predominantly comes from the sea. The first challenge is the spilloverof the competition both in peacetime and wartime. The spillover in peacetime is the claim by Chinaover Indonesia’s territory and EEZ in the South China Sea (SCS). While in wartime is the predictableflood of refugees due to the Sino-India scenario into Indonesian waters; and the expansion of conflictto Indonesia’s territory in the SCS due to the Taiwan scenario.. The second challenge is the risk ofcyber-based hybrid war. This essay argues,with the objective the spillovers are manageable and thecyberthreats are denied, hence, Indonesia should innovate by building up robust air power capable ofcontinual maritime operations, and reinforcing its National Cyber Strategy to protect national security.